Trauma unit management and outcomes at an urban tertiary hospital in sub-Saharan Africa: a descriptive study - Luggya, Tonny Stone; Ngabirano, Annet Alenyo; Sarah, Richardson; Achieng, Lilian; Nabulime, Josephine; Mabweijano, Jackie (African Health Sciences, 2021)
Injuries are a neglected burden despite accounting for 9% of deaths worldwide which is 1.7 times that of hiv, tb and malaria combined. Trauma remains overlooked as research and resources are focused on infectious diseases. Uganda with limited trauma epidemiological data has one of the highest traumatic injury rates. This study describes demographics, management and outcomes of patients admitted to mulago hospital trauma unit. This study was a retrospective record review from july 2012 to december 2015. A data collected included age, time and vitals of admission plus interventions, management and outcomes after which it was analyzed. 834 patient records were reviewed. The predominant age group was 18-35 and 86% of the patients were male. 54% of the patients presented during day and majority of the admission had gcs of less than 8. Antibiotics were given to 467 patients with mechanical ventilation (301) and intubation (289) as the frequent interventions done. 52% of admitted patients were discharged and 40% died. Most admissions’ were of youthful age and had severe head injuries (gcs<8). 56% received antibiotics with frequent interventions beig mechanical ventilation and intubation. 52% of admitted patients were discharged and 40% died.